The carpenter : a story about the greatest success strategies of all - Gordon, Jon, 1971- (Hoboken, New Jersey : Wiley, 2014)
"Bestselling author Jon Gordon returns with his most inspiring book yet--filled with powerful lessons and the greatest success strategies of all. Michael wakes up in the hospital with a bandage on his head and fear in his heart. The stress of building a growing business, with his wife Sarah, caused him to collapse while on a morning jog. When Michael finds out the man who saved his life is a carpenter he visits him and quickly learns that he is more than just a carpenter; he is also a builder of lives, careers, people, and teams. As the carpenter shares his wisdom, Michael attempts to save his business in the face of adversity, rejection, fear, and failure. Along the way he learns that there's no such thing as an overnight success but there are timeless principles to help you stand out, excel, and make an impact on people and the world. Drawing upon his work with countless leaders, sales people, professional and college sports teams, non-profit organizations and schools, Jon Gordon shares an entertaining and enlightening story that will inspire you to build a better life, career, and team with the greatest success strategies of all. If you are ready to create your masterpiece, read The Carpenter and begin the building process today."--Provided by publisher.
"Drawing upon his work with countless leaders, sales people, professional and college sports teams, non-profit organizations, and schools, Jon Gordon shares an entertaining and moving story that will inspire you to build a better life, career, and team with the greatest success strategies of all"--
Collapse -- Rest -- The carpenter -- Stressed -- Busy -- Design your masterpiece -- Be a craftsman -- You will know -- Everybody loves The carpenter -- Believe -- Talk to yourself instead of listening to yourself -- Sarah -- Chaos -- The greatest success strategy of all -- Love is a commitment -- People > Furniture -- The second greatest strategy of all -- The sandwich -- The third greatest strategy of all -- Love, serve, care -- Value -- The heart of success -- Failing -- Success takes time -- The gift of failure -- Unfinished work -- Courage -- A glimmer of hope -- Be the mission -- All for one -- Progress -- Everything is spiritual -- Creating the impossible -- Build -- Success is meant to be shared -- Tools for success -- Bring the greatest success strategies to your team and organization.
Machine generated contents note: Collapse Rest The Carpenter Stressed Busy Design your Masterpiece Be a Craftsman You will Know Everybody Loves The Carpenter Believe Talk to Yourself instead of Listen to Yourself Sarah Chaos Love all of it Love is a Commitment People > Furniture The Second Greatest Strategy of All The Sandwich The Third Greatest Strategy of All Love, Serve, Care Value The Heart of Success Failing Success Takes Time The Gift of Failure Unfinished Work Courage A Glimmer of Hope Be the Mission All for One Progress Everything is Spiritual Creating the Impossible Build Success is meant to be shared.
Keywords: Success in business; Success; Self-actualization (Psychology); Positive psychology